Experimental analysis of an electromagnetic zero-sequence suppressor - De Freitas, S. C L [UNESP]; De Oliveira, L. C O [UNESP]; De Souza, J. B. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The intent of this paper is to present contributions focused on the analysis and development of harmonic attenuator devices. Among these, highlights here the so-called electromagnetic zero-sequence suppressor. This arrangement consists of a filter and a blocker, both electromagnetic, whose combined operation provides paths for low and high impedance, respectively, which can be conveniently adjusted to the desired performance. In this context, here are present results related to experimental studies that show the behavior of the equipment in front of different operating conditions. The tests were performed on a low-power prototype (1kVA/220V) and the analysis results show the main motivator aspects for the use of these devices. © 2012 IEEE.
Keywords: electromagnetic suppressor; experimental analysis; zero-sequence harmonics; Combined operations; Experimental analysis; Experimental studies; High impedance; Low Power; Operating condition; Exhibitions; Electromagnetism